EKRANISASI CERPEN FILOSOFI KOPI KARYA DEWI LESTARI (DEE) KE DALAM FILM FILOSOFI KOPI SUTRADARA ANGGA DWIMAS SASONGKO SEBAGAI ATERNATIF BAHAN AJAR DI SEKOLAH MENENGAH ATAS - Sri Widayati (Universitas Muhammadiyah Kotabumi, 2018)
The core of the research is ekranisasi of short story Filosofi Kopi becomes the film of Filosofi Kopi. The aim of the research is to describe ekranisasi of short story Filosofi Kopi becomes film of Filosofi Kopi. The result of the research shows that there is enkranisasi shorthenage, addition, and the change of the plot of story, setting, and characters in the form of short story becomes film. Short story and film of Filosofi Kopi can be used as a choice of literature learning, especially learning of ekranisasi because to fulfill criteria of the choice of learning material such as language, psychology, and culture.